Taking a Team Approach: Keep Up with the EHR with a Training and Optimization Program - McEntee, Rachel K.; Hitt, Juvena R.; Sieja, Amber (Applied Clinical Informatics, 2025)
Objectives This study aimed to describe the current landscape of electronic health record (EHR) training and optimization programs (ETOPs) and their impact on health care workers' (HCWs) experience with the EHR.Methods A 72-question electronic survey was developed and distributed to health care organization (HCO) leaders in clinical informatics (Chief Medical Information Officer [CMIO]/Chief Nursing Information Officer [CNIO]/Medical Informatics Executive, Associate CMIO/Medical Director of, Clinical/Nurse/Physician Informaticist) through various channels such as national informatics conferences, social media, and email distribution lists of vendors and informatics associations. The survey collected data on the characteristics, resourcing, approach, and outcomes of ETOPs. Descriptive statistics were applied to analyze the data.Results There were 193 responses from 147 distinct HCOs. Of these, 69% offer ongoing EHR training, and 52% offer some version of an ETOP. Offered ETOPs vary in their timing, modality, audience, team composition, duration, and EHR build strategy. The most commonly measured outcomes were EHR satisfaction, efficiency, and provider burnout, and most ETOPs reported improvement in these areas.Conclusion The findings suggest that ETOPs are inconsistently implemented across HCOs, and while there are some commonalities, there is a wide variety of designs and methods of evaluation for the programs. Though the problems to solve (EHR efficiency, proficiency, and satisfaction) are the same, the organizational structure and culture of HCOs vary widely, which may partially explain the variability seen in reported ETOPs. When considering the measured outcomes, ETOPs may have direct and indirect effects on HCW burnout by improving EHR efficiency and satisfaction, as well as driving organizational culture toward teamwork and flexible problem-solving. For this reason, ETOPs may also serve as a model for addressing other challenges in health care delivery. ETOPs are a promising intervention to enhance HCW experience with the EHR and reduce burnout. More research is needed to identify the optimal features, methods, and outcomes of ETOPs, and to disseminate them across HCOs.
Keywords: clinical informatics; electronic health record; burnout; health care workers; organizational culture